Importancia Del Conocimiento Sobre El Pilar Solidario De La Reforma Pensional En Colombia (2024)
The solidarity pillar began with Bill 293, which led to Law 2381 (2024), establishing a regulatory framework for people in situations of poverty, extreme poverty, and vulnerability. The solidarity pillar has been an essential component in pension reform, aiming to provide a basic solidarity income for the elderly who do not have sufficient income to offer a better quality of life. The pillar is directed at men over 65 years old, women over 60 years old, and also for men over 55 years old, women over 50 years old with disabilities, ensuring that those who meet the aforementioned conditions receive economic support.